The Europeanization of Greek Identity - Kınayyiğit, Batu (My University, 2010)
Avrupa Birliği üyeliği Yunanistan’ı çok büyük boyutta değiştirmiştir. Ekonomi ve siyasetin ötesinde, Avrupa Birliği politika ve standartları Yunan milli kimliğini de etkilemektedir. Avrupa Birliği’nin insan hakları, dini haklar ve azınlık hakları konusundaki prensip ve özeni geleneksel Yunan ulusal kimliği anlayışı ile çelişmektedir. Yunanistan tarihsel olarak milli kimliğini etnik ve dini birliğe dayandırmaktadır. Öte yandan Avrupa Birliği üyeliği ve Yunan toplumundaki diğer büyük değişiklikler yeni bir Yunan milli kimliği tanımına yol açmaya başlamıştır.

Accession to the European Union has drastically changed Greece. Beyond major transformations in economy and politics, the European Union policies and standards are also affecting the national identity of Greece. The European Union principles and emphasis regarding human, religious and minority rights are arguably in contradiction with the traditional understanding of Greek national identity. Greece has long based its national identity on ethnic and religious uniformity. However, the European Union membership and other major changes in Greek society have begun to pave the way to a new definition of Greek national identity.
Keywords: Avrupa Birliği_Yunanistan